Hubungan Kegiatan Menggambar Dengan Perkembangan Motorik Halus Anak Usia Dini 5-6 Tahun Di Paud Anak Ceria Desa Parbaju Julu Kec. Tarutung - Losari Aritonang; Adiani Hulu; Endang Junita Sinaga (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
The aim of this research is to determine the relationship between drawing activities and the fine motor development of young children aged 5-6 years in PAUD Anak Ceria, Parbaju Julu Village, Tarutung District. The method used in this research is descriptive quantitative research method. Population is all children u sia d this 5-6 years class B at Ceria Children's Early Childhood Education Center in Parbaju Village Julu District of Tarutung, totaling 18 people. Data was collected using an observation sheet of 20 items. Based on the results of the study, namely the calculation results of a positive relationship test, the value of rxy= 0.483 was obtained > rtable( =0.05,n=18)= 0.468 Thus it is known that there is a positive variable X between variable Y. 2) A significant relationship obtained a value of tcount= 2.204 > ttablel(=0,05,dk=n-2=16)= 2.120, thus there is a significant relationship between variable X and variable Y. So Ha says there is a relationship between activities drawing with fine motor development for early childhood 5-6 years in Ceria Children’s PAUD, Parbaju Julu Village, Tarutung District and H0¬ was rejected.